Technologies and freedom of speech: a reflection on the function of personality rights in the information society - Vince, Fernando Navarro (2020)
New technologies have made it possible to disseminate knowledge, creation and innovation. Within this environment, the Internet stands out, presented as an unparalleled instrument of freedom of speech, but used as a mechanism of control and centralization of power by economic actors and state agents. The objective of this article is to examine the adaptation of personality rights to the new social reality, more precisely, to investigate how freedom of expression has been established in the face of this ambivalence (freedom and control) determined and guided by the complexity of society. Bibliographic research was developed, using the deductive approach method, starting from a generic analysis and confirming, in the specific case, the prominence of freedom of expression in the virtual context. It was concluded that the preservation of freedom of expression is fundamental for the realization of democratic ideals, however, new protection mechanisms will not be necessary, but the strengthening of the existing ones duly adapted to the new informational scenario.